Resolução de uma integral através de métodos numéricos: regra dos trapézios repetida e adaptativa - PONTES, Edilene Lacerda (2022)
The objective of this research was to present and compare the resolution of a simple integral through the numerical method of the repeated and adaptive trapezoidal rule. In this context, the mathematical theories that support these procedures were presented, including the truncation error and the adaptive trapezoidal quadrature algorithm. Initially, the analytical resolution of a simple integral defined in a non-contextualized problem situation was approached, which was later solved numerically through two codes implemented in a Matlab program interface, thus enabling a quantitative analysis through the relative error regarding the performance of the numerical techniques addressed.